Analysis of Entrepreneurial Motivation on Entrepreneurial Psychology in the Context of Transition Economy - Shi, Baisheng; Wang, Tao (Frontiers in Psychology, 2021)
This study aims to explore the connotation of entrepreneurial motivation in the context of a transitional economy. The actual situations of 135 young entrepreneurs are investigated based on questionnaire surveys and case analyses. The influences of different entrepreneurial motivation factors on entrepreneurial psychology are analyzed. Results demonstrate that the item of “gain wealth” on the entrepreneurial motivation scale has the highest score of 3.98 points. In contrast, the scores of opportunity motivation and survival motivation are basically the same, with great differences between different individuals. The dimensions of policies, regulations, and government functions on the entrepreneurial environment scale have high ranks and levels, while the support of industry associations needs to be strengthened. Generally, the entrepreneurial psychology scale has high scores; most of the items score above 3.45 points, indicating that entrepreneurship not only improves the quality of work and life for young entrepreneurs but also promotes the personal growth of entrepreneurs. The multiple stepwise regression analysis reveals significant correlations between survival and opportunity motivations of young entrepreneurs and their subjective psychology and social psychology. The results can provide experimental and useful reference materials for the following investigations.